Isolation and Identification of Organics-Degrading Bacteria From Gas-to-Liquid Process Water - Surkatti, Riham; Al Disi, Zulfa A.; El-Naas, Muftah H.; Zouari, Nabil; Van Loosdrecht, Mark C. M.; Onwusogh, Udeogu (Frontiers in Bioengineering and Biotechnology, 2021)
The gas-to-liquid (GTL) process generates considerable amounts of wastewater that are highly acidic and characterized by its high chemical oxygen demand (COD) content, due to the presence of several organic pollutants, such as alcohols, ketones, aldehydes, and fatty acids. The presence of these organics in the process water may lead to adverse effect on the environment and aquatic life. Thus, it is necessary to reduce the COD content of GTL process water to an acceptable limit before discharging or reusing the treated water. Due to several advantages, biological treatment is often utilized as the main step in GTL process water treatment plants. In order to have a successful biotreatment process, it is required to choose effective and suitable bacterial strains that have the ability to degrade the organic pollutants in GTL process water. In this work, bacterial strains were isolated from the GTL process water, identified by 16S rRNA gene sequencing and then used in the biodegradation process. The detailed identification of the strains confirmed the presence of three organics-degrading bacteria identified as Alcaligenes faecalis, Stenotrophomonas sp., and Ochrobactrum sp. Furthermore, biodegradation experiments were carried out and confirmed that the pure culture as well as the mixed culture consortium of the bacterial strains has the ability to reduce the organic pollutants in GTL process water. However, the growth rate and biodegradation efficiency depend on the type of strains and the initial COD content. Indeed, the removal percentage and growth rate were enhanced after 7 days for all cultures and resulted in COD reduction up to 60%. Moreover, the mixed culture of bacterial strains can tolerate and treat GTL process water with a variety of ranges of COD contents.